Compositional analysis of mole cricket (Gryllotalpa Orientalis Burmeister) II. physico-chemical properties and mineral content - Deveza, Genevieve F.; Dumelod, Benelyn Domingo (2000.)
Some physico-cehmical properties and minerals in raw, preprocessed and cooked mole cricket (Gryllotalpa orientalis Burmeister) were analyzed. The physico-chemical properties - length, color, pH, titratable activity, as well as the amonuts of twelve mineral - calcium, chromium, copper, cobalt, iron, magnesium, manganese, potassium, sodium, zinc, phosphorus, and chloride, were assessed. Analysis of Variance (α= 0.05) showed significant differences among the mean values for length of raw, preprocessed and cooked samples. The color appeared generally brown, with little variation. The pH values and total titratable acidity of the raw sample was reduced significantly with preprocessing but slightly increased after cooking. The water activity of the cooked sample was significantly lower than those of the raw and preprocessed samples. Atomic Absorption Specrophotometry, Molybdovanadophosphate Methos and Mohr Titration of Slat were used to determine the amounts of the different minerals in the samples, absed on wet and dry weight bases. No trend was observed in terms of the gains or losses of minerals due to the effects of processing. Phosphorus was consistently abundant among all the minerals. Sodium was found to be highest in the cooked sample. The cooked sample also contains appreciable amounts of copper, iron and manganese.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Mole cricket -- Analysis